2017
DOI: 10.1186/s13058-017-0837-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine therapy initiation, discontinuation and adherence and breast imaging among 21-gene recurrence score assay-eligible women under age 65

Abstract: BackgroundAside from chemotherapy utilization, limited data are available on the relationship between gene expression profiling (GEP) testing and breast cancer care. We assessed the relationship between GEP testing and additional variables and the outcomes of endocrine therapy initiation, discontinuation and adherence, and breast imaging exams in women under age 65 years.MethodsData from five state cancer registries were linked with claims data and GEP results. We assessed variables associated with survivorshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
7
2
Order By: Relevance
“…We hypothesized that if persistence with medication is motivated in part by an understanding of risk, the 10 years recurrence risk as estimated by Oncotype-DX may be influential. Others have shown the influence of recurrence score on initiation of endocrine therapy [46] however did not find Fig. 4 Clinical management of bothersome symptoms attributed to endocrine therapy in persistent versus non-persistent patients.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We hypothesized that if persistence with medication is motivated in part by an understanding of risk, the 10 years recurrence risk as estimated by Oncotype-DX may be influential. Others have shown the influence of recurrence score on initiation of endocrine therapy [46] however did not find Fig. 4 Clinical management of bothersome symptoms attributed to endocrine therapy in persistent versus non-persistent patients.…”
Section: Discussionmentioning
confidence: 83%
“…We hypothesized that if persistence with medication is motivated in part by an understanding of risk, the 10 years recurrence risk as estimated by Oncotype-DX may be influential. Others have shown the influence of recurrence score on initiation of endocrine therapy [ 46 ] however did not find a significant effect on early discontinuation. In contrast, we found that patients who persisted with endocrine therapy despite bothersome side effects had significantly higher Oncotype Scores compared to patients who discontinued early, although the difference was small (15.9 vs. 13.7, p = 0.028).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[22] Paradoxically, evidence suggests that inaccurate risk perception may be associated with poor treatment adherence and surveillance decisions in survivorship. [23] Following publication of the findings of the TAILORx study, future research should examine the role of GEP testing and risk perceptions on survivorship and surveillance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Between 4% and 30% of women with hormone receptor (HR)‐positive breast cancer who completed primary treatment of early‐stage breast cancer (EBC) do not initiate the follow‐up long‐term adjuvant endocrine therapy (AET) (Berkowitz et al, 2021 ; Kroenke et al, 2018 ; Neugut et al, 2012 ; O'Neill et al, 2017 ), and 15–43% are non‐adherent (i.e., do not take medication as prescribed) (Berkowitz et al, 2021 ; Cavazza et al, 2020 ; Font et al, 2019 ; Lailler et al, 2021 ; Lambert‐Côté et al, 2020 ; Makubate et al, 2013 ; Mislang et al, 2017 ; Murphy et al, 2012 ). AET is used in patients with oestrogen receptor (ER)‐positive EBC for at least 5 years in order to prevent recurrence and reduce the mortality (Cardoso et al, 2019 ; Early Breast Cancer Trialists' Collaborative Group, 2011 ) and comprises the (sequential) use of the selective ER modulator (SERM) tamoxifen and aromatase inhibitors (AIs) like anastrozole, exemestane and letrozole (Burstein et al, 2019 ; Cardoso et al, 2019 ; Parisi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%